CLINTERVENTIONAL protocol: a randomized controlled trial to evaluate clinical consultations and audiovisual tools for interventional radiology - Pedro Blas García Jurado; Juan José Espejo Herrero; María Sagrario Lombardo Galera; María Eugenia Pérez Montilla; Sara Barranco Acosta; José García-Revillo; Pilar Font Ugalde; Marina Álvarez Benito (European Radiology Experimental)
Abstract Interventional radiology (IR) has evolved rapidly, but the clinical integration of interventional radiologists has not kept pace with technical advancements. This trial will address a gap in the literature by providing a robust investigation into specific measures for enhancing the clinical role of interventional radiologists, with potential implications for improving patient experiences and outcomes. The single-center randomized controlled trial will include 428 patients undergoing IR procedures. The control group will receive information about the procedure from the ordering physician, while the experimental group will have an additional consultation with an interventional radiologist and be shown procedure-specific explanatory videos. The primary outcomes are patients’ knowledge, satisfaction with the information and communication, and anxiety. Data collection will involve specific questionnaires and scales. This trial is designed to investigate the importance of proactive clinical roles in patient care within IR. The study explores the potential of consultations and audiovisual tools, highlighting their role in educating patients about procedures. The results may help foster a more widespread acceptance of clinical responsibilities in IR and underscore the pivotal role of audiovisual aids in patient education and satisfaction. Trial registration NCT05461482 at clinicaltrials.gov. Relevance statement This randomized controlled trial will assess the impact of clinical consultations and explanatory audiovisual tools on patient understanding, satisfaction, and anxiety in interventional radiology. The findings could help establish a more proactive clinical role for interventional radiologists and improve the overall quality of patient-centered care. Key Points We describe the protocol of an interventional radiology randomized clinical trial. The control group will receive procedure information from the referring physician and the experimental group receives additional consultation with interventionalists and views a video. Knowledge, satisfaction with information, and patient anxiety will be evaluated. This study will provide insights about the benefits of consultations and videos in interventional radiology. Graphical Abstract